Food Security in Times of Covid-19: Price Aspects in Ukraine and Neighboring EU Countries - Vasylieva, Natalia; Васильєва, Наталя Костянтинівна (University of Montenegro, Podgorica - Faculty of Economics, 2021)
So far, all countries around the world have to deal with the Covid-19 challenge. As imperative, it includes providing food security subject to pandemic restrictions and consequences. The study purpose took focus on exploring price dynamics observed for basic crop and animal products. The research hypothesis supposed different volatility of their prices linked with a certain similarity across the considered Eastern European countries. The utilized methods involved candlestick charting and analysis of variance ANOVA to compare the food price indices and changes in times of the Covid-19 between February and December 2020 with regard to the corresponding pre-Covid-19 period. The research findings revealed stable pricing for bread and cheese with fluctuations below 4%. The study outcomes indicated the most disruptive Covid-19 impact on potato and pork. The latter largely associated with Hungary, Poland, Romania, and Slovakia. Prices for sugar and eggs in Ukraine gained by 46.2% to 30.4% and illuminated unhealthy shifts in dietary patterns. The basic research conclusions are as follows. Firstly, food chains in animal husbandry need special enhancements to face the Covid-19 crisis. Secondly, the evidenced price volatility coupled with the decreasing purchasing power are the reasons to concern on providing balanced nutrition and healthy diets in Ukraine and the neighboring EU countries. Наразі всі країни світу долають Covid-19. Це передбачає підтримку продовольчої безпеки за карантинних обмежень. Дане дослідження сфокусовано на дослідженні цінової динаміки на продукти рослинництва і тваринництва. Гіпотеза дослідження полягала у встановленні подібності цінових коливань у країнах Східної Європи. Застосовані методи побудування свічкових діаграм та дисперсійного аналізу ANOVA за період лютого-грудня 2020 року відносно відповідного період до Covid-19. Дослідженням виявлено стабільність цін на хліб та сир з флуктуаціями до 4%. Найбільшого впливу зазнали ціни на картоплю та свинину, що особливо позначилося в Угорщині, Польщі, Румунії та Словаччині. Ціни на цукор та яйця в Україні зросли на 46,2% і 30,4%, засвідчуючи погіршення складу харчового кошику. У висновку наголошено, що харчові ланцюжки в тваринництві потребують додаткового посилення в умовах кризи, викликаної Covid-19. Проаналізовані цінові коливання разом зі зниженням купівельної спроможності населення засвідчують необхідність додаткової уваги до забезпечення збалансованого харчування в Україні та сусідніх країнах ЄС.
Продовольча безпека в часи Covid-19: цінові аспекти в Україні та сусідніх країнах ЄС
Keywords: Food prices; продовольчі ціни; Covid-19 impact; вплив Covid-19; candlestick charts; свічкові діаграми; analysis of variance ANOVA; дисперсійний аналіз ANOVA; Eastern European countries; країни Східної Європи